Ambient-environment processed perovskite solar cells: A review. (November 2021) - Younas, Muhammad; Kandiel, Tarek A.; Rinaldi, Ali; Peng, Qing; Al-Saadi, Abdulaziz A.
Abstract: A remarkable and fast development has been recently noticed in perovskite solar cells (PSCs). The efficiency of the emerging PCSs has been improved from 3.8% to 25.5% in only about one decade. The outstanding improvement in the performance of PSCs is attributed to perovskites' unique structural properties, high absorption coefficient, tunable band gap, long electron-hole diffusion length, and high charge carriers' mobility. Efficient PSCs devices are normally fabricated at a lab scale in an inert environment with a very small area (∼0.1 cm 2 ). However, for practical applications, there is a need to develop PSCs on a large-scale level in an ambient environment. Recently, enormous efforts have been devoted to design ambient-environment processable PSCs with considerable attention on understanding the impact of moisture and oxygen on their stability and efficiency. In this review, we start by shedding light on the main crystal and electronic properties of PSCs. We then focus on the recent progress in the ambient-environment processed PSCs and detailed the impact of moisture and oxygen on perovskite crystal growth, morphology, and stability. The possible approaches to control the fabrication of efficient and ambient stable perovskite solar cells have been discussed in detail. The available techniques for the development of PSCs at the lab scale with either controlled or ambient environments and at the large scale have been discussed and summarized. This review is finally concluded with a highlight of challenges encountered and pathways to improve the performance, stability, and scalability of PSCs before commercialization. Graphical abstract: Image 1 Highlights: Review focused on the recent progress in the ambient-environment processed PSCs. Discussed the impact of moisture and oxygen on crystal growth, morphology, and stability. Comments on approaches to control the fabrication of efficient and ambient stable PSCs. Outlook challenges encountered and pathways to commercialize PSCs.